A Review on Catalytic Fast Co-Pyrolysis Using Analytical Py-GC/MS - Sabah Mariyam (14150859) (2023)
Py-GC/MS combines pyrolysis with analytical tools of gas chromatography (GC) and mass spectrometry (MS) and is a quick and highly effective method to analyse the volatiles generated from small amounts of feeds. The review focuses on using zeolites and other catalysts in the fast co-pyrolysis of various feedstocks, including biomass wastes (plants and animals) and municipal waste materials, to improve the yield of specific volatile products. The utilisation of zeolite catalysts, including HZSM-5 and nMFI, results in a synergistic reduction of oxygen and an increase in the hydrocarbon content of pyrolysis products. The literature works also indicate HZSM-5 produced the most bio-oil and had the least coke deposition among the zeolites tested. Other catalysts, such as metals and metal oxides, and feedstocks that act as catalysts (self-catalysis), such as red mud and oil shale, are also discussed in the review. Combining catalysts, such as metal oxides and HZSM-5, further improves the yields of aromatics during co-pyrolysis. The review highlights the need for further research on the kinetics of the processes, optimisation of feed-to-catalyst ratios, and stability of catalysts and products. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules28052313